The Nexus of Anthropogenic Climate Change, Primary Energy Consumption and Dynamic Economic Change in India - Wada, Isah (International Journal of Energy Economics and Policy, 2022)
The empirical connection between anthropogenic climate changes, aggregate production index, primary energy consumption, population dynamics, capital formation, and real per capita income in India is investigated in this study. The equilibrium long-run relationship among the studied variables and their causality are analysed using the theoretical framework of Cobb Douglas’s production function. The study used a time series data set from 1965 to 2018 as part of a novel bound testing methodology strongly backed up by the classical cointegration techniques. As a result, the model’s short- and long-run relationships are estimated. The estimation reveals long-run equilibrium convergence between anthropogenic climate change and the remaining exogenous factors empirically examined. Consequently, the aggregated production index, real domestic investment, and real economic growth have both short-run and long-run positive impact in the estimated model. The findings revealed further that primary energy use is the leading cause of anthropogenic climate change, causing changes to real domestic investment and population. A significant policy recommendation, among others, is a faster transition to cleaner energy to combat anthropogenic climate change, owing to India’s extremely high energy intensity power sector with massive primary energy consumption.